Acuerdos comerciales y sus efectos en la balanza comercial entre Perú y paises del Asia, durante el periodo 2000 - 2014 - Canahuire Calipuy, Liliana Lizbeth (2016)
The present study analyzes the trade agreements and their effects on the trade balance between Peru and Asian countries during the period 2000 - 2014. Its objective is to analyze trade agreements and their effects on the trade balance between Peru and Asian countries, during the period 2000 - 2014. This research was developed using information obtained from the annual database of the World Bank (WB), the Association of Exporters (ADEX Data Trade) and the Ministry of Foreign Trade and Tourism (MINCETUR). The procedure followed in the investigation consists of the non - experimental, explanatory and longitudinal analysis, the analytical - synthetic method has been used to decompose the variables and with it to understand the effect of trade agreements on the trade balance recorded in the period 2000 - 2014, the deductive and inductive method to interpret the behavior of the agreements in the variables involved in the investigation, the statistical method to explain the behavior of the variables under study for this will be performed various statistical operations. The hypothesis raised in the research is: "Trade agreements have a positive effect on the trade balance between Peru and the Asian countries during the period 2000 - 2014." The results obtained based on the gravitational model show that trade flows increased between Peru and the Asian countries, being much more favorable for the countries of Singapore, Thailand and Malaysia, but it has not been unfavorable for South Korea. In order to determine these results, trade flow effects have to be added with the countries of China, Japan, Vietnam and India. In this sense the working hypothesis has been accepted